ChemInform Abstract: Dimeric Pyrrole—Imidazole Alkaloids: Synthetic Approaches and Biosynthetic Hypotheses. Issue 36 (9th September 2014) - Wang, Xiao; Ma, Zhiqiang; Wang, Xiaolei; De, Saptarshi; Ma, Yuyong; Chen, Chuo
Abstract Review: [50 refs.